Perspectives in Water Pollution - Ahmad, Imran; Ahmad Dar, Mithas (IntechOpen, 2013)
Water is an important natural resource which forms the core of the ecological system. Human use of water depends on ambient water quality and human alterations of the landuse have an extensive influence on water quality. Water is typically referred to as polluted when its quality is adversely affected by contaminants and undergoes a marked shift in its capability to support the biological communities. The book is written for research scholars, hydrologists and environmentalists and especially students.